2022
DOI: 10.3201/eid2807.220600
|View full text |Cite
|
Sign up to set email alerts
|

Zoster Meningitis in an Immunocompetent Child after COVID-19 Vaccination, California, USA

Abstract: Varicella zoster virus reactivation after COVID-19 vaccination has been reported in older or immunocompromised adults. We report zoster meningitis from live-attenuated varicella vaccine reactivation in an immunocompetent child after COVID-19 vaccination. This type of case is rare; COVID-19 and varicella vaccines remain safe and effective for appropriate recipients in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In line with this, a recent retrospective study found that vaccinated people might show a higher risk of infection than unvaccinated individuals 9 months post-vaccination [ 50 ]. A potential sign of an immunosuppressed state comes from reports of viral reactivations [ 51 55 ] and suspected infections in open-heart surgeries that could not be controlled even with long-term antibiotic treatments, resulting in several deaths [ 56 ]. A surge in candidiasis, aspergillosis, and mucormycosis cases associated with COVID-19 has been reported [ 57 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a recent retrospective study found that vaccinated people might show a higher risk of infection than unvaccinated individuals 9 months post-vaccination [ 50 ]. A potential sign of an immunosuppressed state comes from reports of viral reactivations [ 51 55 ] and suspected infections in open-heart surgeries that could not be controlled even with long-term antibiotic treatments, resulting in several deaths [ 56 ]. A surge in candidiasis, aspergillosis, and mucormycosis cases associated with COVID-19 has been reported [ 57 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…SC2V-related cerebrovascular diseases include VST, ischemic stroke, ICH, SAB, pituitary apoplexy, RCVS, cerebral vasculitis, and Susac syndrome ( Table 2 ) [ 4 , 6 …”
Section: Resultsmentioning
confidence: 99%
“…Herpes zoster following COVID-19 vaccination has been widely reported [ 48 , 49 , 50 , 51 , 52 , 53 ], although conclusive evidence of a direct link is lacking. Table 3 summarises these selected reports.…”
Section: Sars-cov-2 Vaccination and Human Herpesviruses Infectionsmentioning
confidence: 99%